Art Communication and the Museum. Prerequisites of Art Translation Didactics - Jurewicz, Magdalena (2024)
In order to draw attention to the linguistic context concerning fine arts, this paper presents a didactic approach to translation difficulties concerning the reconstruction of the real meaning of interlingual lacunae (gaps), understood as lexical units present in one culture and absent in another, using the example of ambiguous Polish terms referring to a painting style present in albums or museum guides. Based on the model of reconstructing the actual meaning, selected terms related to the existence of the so-called Munich School are shown, which, if not identified correctly, can lead to a trivial interpretation of a given work of art by the audience in the target culture. Language and linguistic actions are essential for the description of works of art, their meaning and cultural-historical references, which is also linguistically manifested in established text types and genres. The reception of art is essentially through two channels: visual and verbal. Observers can identify the content of the work through their own cultural filters, including human universals. The presence of verbal comments can enrich a better and deeper understanding of its meaning. People have been describing the meaning of art verbally since they encountered artefacts rooted in other cultures, but the branch of linguistics dealing with the relationship between language and visual art is very young and consequently little researched. The same applies to the topic of translation in the field of art communication and museums, which is relatively new. The results of the analysis presented in this paper can be used by university translation didacticians and by translators to find adequate equivalents in the field of translation in the field of painting history.
Keywords: regional city museums; advertisements of exhibitions; unambiguous painting style terminology; challenges for translators; “Munich School” of painting